Taking the high road? Compliance with cmmuter tax allowances and the role of evasion spillovers - Jörg Pätzold; Hannes Winner (Austrian Institute of Economic Research (WIFO), 2016)
This paper provides evidence of evasion in the context of a widely used commuter tax allowance, and explores evasion spillovers as a determinant of the individual compliance decision. For this purpose, we exploit discontinuities in the commuter allowance scheme and employ a research design resting on a large panel of individual tax returns. We find that around 30 percent of all allowance claims are overstated and, consistent with deliberate tax evasion, we observe sharp reactions of tax payers to thresholds where the allowance discretely jumps to a higher amount. Further, we use variation in job changes to uncover spillover effects from the work environment on the individual compliance decision. These effects appear to be asymmetric: job changers moving to companies with a higher fraction of cheaters increase their cheating. In contrast, movers to companies with a lower fraction of cheaters tend not to alter their reporting behaviour. We provide suggestive evidence that the spillover has more to do with an information environment, but can ultimately not reject other behavioural explanations such as asymmetric persistence of norms.
Keywords: H24; H26; D83; 330; Tax Evasion; Self-Reporting; Tax Deductions; Spillover Effects